The contributions of art exhibitions to the teaching and learning process in visual arts (Palíndromo, 2025)
School art exhibitions are part of pedagogical practices in visual arts, occupying classrooms and hallways with students' artistic productions displayed on bulletin boards, walls, or panels. Their presence highlights the need to broaden the discussion about the importance of schools having spaces that can be dedicated to showcasing student work, as well as developing activities in galleries, art centers, or museums. But how do school art exhibitions contribute to the teaching and learning process in visual arts? Do they establish a relationship with exhibition spaces outside the school? In what way? Based on a historical and critical approach, we conducted a literature review aiming to understand how school art exhibitions contribute to the teaching and learning process in visual arts, evaluating the relationship between these practices and exhibition spaces outside the school environment. The results indicate that exhibitions represent a teaching and learning strategy in visual arts that helps bring the art world into the school, focusing on the school's own reality by creating environments that allow for the display of students' artistic productions, in accordance with their context. These actions promote closer ties between students, teachers, and the school community, strengthening affective bonds and reinforcing pedagogical and aesthetic intentions. They also indicate the need for systematized actions that integrate digital platforms, contemporary art, and exhibition spaces, both inside and outside the school.
Keywords: visual arts; school; exhibition space